The 16 sixteen personality types: description for self-discovery/ Linda V. Berens and Dario Nardi - "Berens, Linda V." (California, 1999)
The 16 Personality Types, Descriptions for Self-Discovery is an invaluable tool for users of the MBTI and related instruments. These descriptions present a living systems approach to describing the 16 types. Dr. Berens and Dr. Nardi have captured the essence of the 16 type patterns and crafted descriptions to be used to by individuals to clarify their best-fit type. This booklet provides the user with . . . * an interactive process to help individuals clarify their own best-fit type. * worksheets to help individuals better understand themselves and others. * a brief description of the themes for each type pattern * a snapshot for each type pattern * a full page Portrait for each type pattern--written in third person * a full page Self-Portrait-the long awaited Self-Discovery Descriptions - written in 1st Person * appendices for a brief overview of temperament, interaction styles, and type dynamics and development. From the Back Cover "Knowing others is intelligence; knowing yourself is true wisdom. Mastering others is strength; mastering yourself is true power." - Lao Tzu Like trees in a forest, we are ever changing . . .yet staying the same . . .weathering the seasons of life. Coming to understand who we are is like looking into a lake. Sometimes the lake is so clear the reflection is nearly perfect, and we can't tell what is "real" and what is reflected. Other times, as in life, the lake is choppy. We only see a resemblance of ourselves, or we recognize nothing at all. Self-reflection can help us know ourselves, but may lead us in circles. Likewise, personality tests aren't always accurate. They are, like the choppy lake, subject to the winds of change, often reflecting our basic pattern but sometimes misleading us. Friends, family, and co-workers can give us valuable feedback but see us through their own lenses--sometimes, only giving us clues. Only by integrating all of these methods can we find our best-fit personality type pattern. The Sixteen Personality Types, Descriptions for Self-Discovery engages you in a self-discovery process using multiple forms of feedback. This process of uncovering and revealing requires your active participation. This book is designed to help you actively participate in your own self-discovery process. Accurate identification of our best-fit personality type pattern is the first step in mastering ourselves. Without it, we can delude ourselves. With it, we can find true insight, wisdom, security and freedom.
Keywords: Personality